An On‐Chip Second‐Order Elastic Topological Insulator for Demultiplexing Out‐of‐Plane and In‐Plane Corner Modes - Yafeng Chen; Lei Fan; Jie Zhu; Zhongqing Su (Advanced Science)
Abstract Second‐order elastic topological insulators (SETIs) with tightly localized corner states present a promising avenue for manipulating elastic waves in lower dimensions. However, existing SETIs typically support corner states of only a single mode, either out‐of‐plane or in‐plane. In this work, an on‐chip SETI that simultaneously hosts both high‐frequency out‐of‐plane and in‐plane corner states at ≈0.2 MHz is introduced. The presence of these corner states is experimentally validated, and their selective excitation by tuning the excitation frequency is demonstrated. This capability to demultiplex out‐of‐plane and in‐plane corner states positions the SETI as a potential platform for developing multifunctional elastic devices and enhancing the communication capacities of elastic waves. Furthermore, due to its structural simplicity, the SETI can be readily scaled and integrated into on‐chip elastic circuits, making it suitable for applications in micro‐electromechanical systems.